Forage And Grain Productivity, Quality And Economics Of Some Maize (Zea Mays L.) Varieties (Applied Biological Research, 2015)
The present study was aimed to find out the superiority amongst  different use patterns in maize crop for higher yield, forage nutritional  quality and profit. Three maize varieties each of baby corn, green cob,  seed type and four forage type were grown together under field  condition in kharif season 2011 and 2012. The mean green forage yield  obtained from maize forage type was approximately 1.70 times higher  than baby corn and seed type cultivars and 2 times than those of green  cob type cultivars. The mean dry matter yield of forage type maize was  1.75, 1.60 and 1.35 times higher than baby corn, green cob and seed  type, respectively. Forage type maize cultivar ‘African Tall' gave  significantly highest green forage yield, dry matter yield and crude  protein yield. The highest mean per cent crude protein (8.5%), crude  protein yield (7.38 q ha-1) and in vitro dry matter digestibility (58.7%)  with the lowest mean crude fibre content (22.0%) and acid detergent  fibre (43.0%) was observed in forage type maize. The lowest mean  neutral detergent fibre (62.7%) and highest mean gross monetary  returns, net monetary returns, B: C (3.5) and fodder equivalent yield  was found in baby corn type maize cultivars. In conclusion, growing  fodder type cultivars were suitable for producing more fodder yield with  better nutritional quality; however, the baby corn type cultivars for  earning the highest net profit along with fodder under limited land  resources.
Keywords: Baby corn; economics; forage quality; maize-use patterns; yield